Audit Manajemen Sumber Daya Manusia pada BUMK Universitas Muhammadiyah Riau: Studi Kasus UMCO - Fadhil Hafizh Nabil; Sabrina Faylesia; M. Aprialdi Pratama (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effectiveness of human resource management at the University-Owned Enterprise (BUMK) of Universitas Muhammadiyah Riau (UMCO) through a Human Resource Management Audit approach. The study employed a qualitative method using a case study design. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data presentation, conclusion drawing, and the formulation of audit recommendations. The findings indicate that the human resource management functions at UMCO have generally supported organizational operations, including workforce planning, recruitment and selection, training, performance appraisal, compensation, and internal control. However, the audit identified several weaknesses, including the absence of a formal Human Resource Planning (HRP) system, a lack of Standard Operating Procedures (SOPs) and competency standards, unstructured training programs, performance appraisal systems that are not based on measurable indicators, and human resource administration that is not supported by an integrated Human Resource Information System (HRIS). Therefore, implementing the audit recommendations is expected to enhance the effectiveness of human resource management, strengthen organizational governance, and support the sustainability of UMCO as a university-owned enterprise.